Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acs.jpclett.9b03829
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Electron–Phonon Interaction of Topological Semimetal Surfaces Measured with Helium Atom Scattering

Abstract: He atom scattering has been demonstrated to be a sensitive probe of the electron−phonon interaction parameter λ at metal and metal-overlayer surfaces. Here it is shown that the theory linking λ to the thermal attenuation of atom scattering spectra (the Debye−Waller factor) can be applied to topological semimetal surfaces, such as the quasi-onedimensional charge-density-wave system Bi(114) and the layered pnictogen chalcogenides. The electron−phonon coupling, as determined for several topological insulators bel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 58 publications
3
43
0
Order By: Relevance
“…This might not be the case on a surface where specific vibration modes exist 86 that are localized close to the surface. Using a slab approach of the surface, Schram and Heller 87 suggested that the initial excitation could indeed dilute in many phonon modes and that the apparent quasi-elastic diffraction could, in part, be due to the excitation of very low energy mode having a negligible contribution to the angular and energy straggling.…”
Section: Quantum Binary Scatteringmentioning
confidence: 99%
“…This might not be the case on a surface where specific vibration modes exist 86 that are localized close to the surface. Using a slab approach of the surface, Schram and Heller 87 suggested that the initial excitation could indeed dilute in many phonon modes and that the apparent quasi-elastic diffraction could, in part, be due to the excitation of very low energy mode having a negligible contribution to the angular and energy straggling.…”
Section: Quantum Binary Scatteringmentioning
confidence: 99%
“…14,15 Since the thermal attenuation of any quantum peak feature in the atom scattering spectra is due to an average over the mean square displacement of all phonon modes weighted by the respective electron-phonon coupling, it is not surprising that such attenuation can be related to the average l HAS = hl Q,n i. [16][17][18][19] This will be discussed in more detail below in Section 2 where the theory is briefly outlined. In Section 3 values of l HAS are obtained from the available He atom scattering data on C(0001).…”
Section: Introductionmentioning
confidence: 99%
“…tion regime[83][84][85] including modifications of the surface electronic structure via adsorption[86][87][88][89] and effects relevant for heterogeneous catalysis or sensing applications90,91 .4 | 1-15 J o u r n a l N a me , [ y e a r ] , [ v o l . ] ,…”
mentioning
confidence: 99%